2007
DOI: 10.1016/j.neucom.2006.10.124
|View full text |Cite
|
Sign up to set email alerts
|

Switching between gamma and theta: Dynamic network control using subthreshold electric fields

Abstract: We implemented an experimentally observed orthogonal arrangement of theta and gamma generation circuitry in septotemporal and lamellar dimensions is a two-dimensional model of hippocampus. The model includes three types of cells: pyramidal, basket, and oriens lacunosum-moleculare (OLM) neurons. In this reduced model, application of continuous electric fields allowed us to switch between theta, gamma and mixed theta-gamma regimes without additional pharmacological manipulation. Electric field effects on individ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
10
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 18 publications
3
10
0
Order By: Relevance
“…EF effects at the level of single cells in the model are consistent with previous experimental observations [2,7]. Results obtained in our previous model [5] are reproduced.…”
Section: Methods and Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…EF effects at the level of single cells in the model are consistent with previous experimental observations [2,7]. Results obtained in our previous model [5] are reproduced.…”
Section: Methods and Resultssupporting
confidence: 90%
“…It has been proposed that theta modulation can synchronize cell assemblies across the hippocampus; that place cell firing phase can code for the animal position; and that different phases of theta correlate with learning vs. recall. To demonstrate control of theta and gamma rhythms by electric field (EF), we developed a simplified 2-dimensional CA1 network based on [4] showing theta-modulated high frequency activity of pyramidal neurons [5]. Application of EF alone was able to shift the firing mode of the simplified network in the theta-gamma range.…”
mentioning
confidence: 99%
“…On one hand, the electromagnetic radiation of organism environment is strengthening rapidly and the phenomenon of induced neurological disease becomes increasingly common because external electric affects the function of nervous system; on the other hand, electrical stimulation has become one of the main experimental means of neurological diseases treatments [16]. Many experiments confirmed that external electric field can affect the dynamic characteristics of neurons [17][18].…”
Section: Consider Micro External Electric Fieldsmentioning
confidence: 99%
“…The object of this study, which is the neuron model brought up by Sherman in 1988 [16], analyzed the influence of different parameters to model discharge rhythm through changing parameters in the model to analyze the model dynamic characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…KInNeSS records the voltage of individual compartments, as well as aggregate cell recordings such as local field potentials (LFP) and current source densities (CSD). Typical simulations that have been performed by KInNeSS include models of hippocampal neurons and spatial navigation , models of thalamo-cortical learning Leveille et al, 2008), and models of interactions between electric field and cell activity (Berzhanskaya et al, 2007).…”
Section: Kinness Overviewmentioning
confidence: 99%